THE EFFECT OF FINANCIAL COMPENSATION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE WORK DISCIPLINE PT DIALOGUE GARMINDO UTAMA MEDAN - Yusuf Taufik; Wie Shi Wudjud (PT. MITRA ANGKASA INFORMATIKA, 2024)
Dialogue Garmindo Utama is a distribution company and distributor engaged in textiles and garments with marketing targets throughout Indonesia. Products sold by PT. Dialogue Garmindo Utama is in the form of baby equipment such as sling bags, pillows, baby bags, mattresses, aprons, blankets, milk bottles, mommy bags, etc. and also sells household supplies such as doormats, napkins, tablecloths and others. The method used in this research is quantitative analysis method. The population in this study was 60 people. The types of data used in this study are primary data and secondary data. This data was collected through interviews and questionnaires. This study uses saturated sampling by taking all population numbers as samples to be tested using SPSS. The scale used to measure variables is using the Likert scale. The data analysis technique used is multiple linear regression. Based on the results of testing financial compensation and organizational commitment influences the work discipline of employees of PT. Main Garmindo Dialogue. Partial test results, the results of this study state that financial compensation has a significant effect on the work discipline of employees of PT. Dialogue Garmindo Utama rather than organizational commitment Keywords: Financial Compensation, Organizational Commitment, Work Discipline